(untitled) (Global Journals of Research in Engineering, 2012)
In the urban environment due to the rapid rate of urbanization and industrialization, it needs proper planning, management and requires up-to date digital spatial information for multifaceted applications with higher accuracy. Digital photogrammetry provides maps and databases to support decision-making and futuristic planning as well as to access the utility services in urban areas for civilians well being. The objective of the study is to access the various urban utilities for civilian#x2019;s wellbeing and develop a 3D model of the area for planning and monitoring of Dahisar urban area of Mumbai City. Cadastral map (G F/15) and utility information from National Informatics Centre (NIC) has been used to assess household information with each building details. Aerial stereo pairs are used to generate 3D model after data processing and orthorectification by applying LPS software. Attribute data has been attached to each building as a separate layer by using ArcGIS software. Land use / land cover classification has been carried out to identify various utility services sectors like school, hospital, banks, public toilets, commercial area, bus stops etc. The utilities like school and bank are better towards western and south-western part. In Dahisar region, residential area dominates with respect to other type of land use. Hospital services are poor in Dahisar region and there is urgent need to establish some new hospitals in the area. Vertical growth of the city shows that 41% buildings in Dahisar region are above 30 meter height. 3D city model of the area gives the precise information of the area which can be used for urban planning and development.